Real-World Analysis of Survival and Clinical Events in a Cohort of Italian Perinatally HIV-1 Infected Children From 2001 to 2018 - Chiappini, Elena; Larotonda, Francesca; Lisi, Catiuscia; Giacomet, Vania; Erba, Paola; Bernardi, Stefania; Zangari, Paola; Di Biagio, Antonio; Taramasso, Lucia; Giaquinto, Carlo; Rampon, Osvalda; Gabiano, Clara; et al. (Frontiers in pediatrics, 2021)
Background: Combined antiretroviral therapy (cART) has been associated with a steep decrease in mortality and morbidity in HIV-1 infected children. New antiretroviral molecules and drug classes have been developed and the management of HIV-infected children has improved, but recent data on survival are limited. Methods: An observational retrospective study investigating changes in mortality and morbidity was conducted on 1,091 perinatally HIV-1 infected children enrolled in the Italian Register for HIV Infection in Children and followed-up from 2001 to 2018. Results: Three hundred and fifty-four (32%) AIDS events and 26 (2%) deaths occurred overtime. Mortality rates decreased from 0.4/100 person-years in 2001–2006 to 0.27/100 person-years in 2007–2012 and 0.07/100 person-years in 2013–2018. Notably, 92% of the dead children were born in Italy, but only 50% were followed-up since birth or within three months of age. Seventy three percent of children had started cART at age ≥6 months; 23% were treated for <30 days before death. B and C clinical events progressively decreased ( P < 0.0001). Opportunistic infections significantly decreased over time, but still were the most common events in all the periods (6.76/100 person-years in 2013–2018). In the last period, severe bacterial infections were the most common ones. Cancer rates were 0.07/100; 0.17/100; 0.07/100 person-years in the three periods, respectively. Conclusions: Progressive reductions both in mortality and in rates of class B and C clinical events and OIs have been observed during the cART era. However, deaths were still registered; more than half of dead children were enrolled after birth and had belatedly started cART.